Convergent Evolution among Ruminant-Pathogenic Mycoplasma Involved Extensive Gene Content Changes. (8th August 2018) - Lo, Wen-Sui; Gasparich, Gail E; Kuo, Chih-Horng
Abstract: Convergent evolution, a process by which organisms evolved independently to have similar traits, provides opportunities to understand adaptation. The bacterial genus Mycoplasma contains multiple species that evolved independently to become ruminant pathogens, which represents an interesting study system for investigating the process. In this work, we determined the genome sequences of 11 Entomoplasma / Mesoplasma species. This new data set, together with the other available Mollicutes genomes, provided comprehensive taxon sampling for inferring the gene content evolution that led to the emergence of Mycoplasma Mycoides cluster. Our results indicated that the most recent common ancestor (MRCA) of the Mycoides-Entomoplasmataceae clade lost ∼15% of the core genes when it diverged from the Spiroplasma Apis clade. After this initial wave of genome reduction, relatively few gene gains or losses were inferred until the emergence of the Mycoides cluster. Compared with those Entomoplasmataceae lineages that maintained the association with insects, the MRCA of the Mycoides cluster experienced a second wave of gene losses, as well as acquiring >100 novel genes through horizontal gene transfer. These gene acquisitions involved many with the Mycoplasma Hominis/Pneumoniae lineages as the putative donors, suggesting that gene exchanges among these vertebrate symbionts with distinct phylogenetic affiliations may be important in the emergence of the Mycoides cluster. These findings demonstrated that the gene content of bacterial genomes could be exceedingly dynamic, even for those symbionts with highly reduced genomes. Moreover, the emergence of novel pathogens may involve extensive remodeling of gene content, rather than acquisition of few virulence genes.